Agricultural Exports from Latin America and the Caribbean : Harnessing Trade to Feed the World and Promote Development - Chaherli, Nabil (World Bank, Washington, DC, 2013)
The United Nations estimates that global food demand will double by 2050, with much of that growth in developing countries. The world will have 2.3 billion more people, and given the deep transformation of growth trajectories in low-income countries, they will be increasingly affluent, with demands for more, different, and better food. While countries in Latin America and the Caribbean (LAC) are quite heterogeneous in their production potential, overall they are well equipped to contribute to meeting this challenge. LAC has always maintained a strong comparative advantage in agricultural production, as indicated not only by its position as a net food exporter but also by its high comparative advantage. LAC is also well endowed in renewable water resources, with about a third of the 42,000 cubic kilometers worldwide. Per capita, LAC has the highest endowment of renewable water among developing regions, though some sub regions in LAC face higher than average scarcity. This report's in-depth look at Argentina and Brazil identifies looming logistics and policy issues that threaten to derail these locomotives of agricultural growth and some policy choices that have contributed to their success and that might be worth emulating. While LAC countries have substantially reduced the anti-export and anti-agricultural biases in their trade regimes, this bias remains significant in some countries. Argentina, a major food exporter, imposes export taxes and quantitative controls, with considerable adverse consequences for the sector and the global food trade system. For LAC countries' agricultural sectors to stay competitive, it is important to appropriately manage the real exchange rate to minimize Dutch disease.